Application of Metagenomic Next-Generation Sequencing in Mycobacterium tuberculosis Infection - Li, Yaoguang; Jiao, Mengfan; Liu, Ying; Ren, Zhigang; Li, Ang (Frontiers in Medicine, 2022)
The fight against Mycobacterium tuberculosis (MTB) has been going on for thousands of years, while it still poses a threat to human health. In addition to routine detections, metagenomic next-generation sequencing (mNGS) has begun to show presence as a comprehensive and hypothesis-free test. It can not only detect MTB without isolating specific pathogens, but also suggest the co-infection pathogens or underlying tumor simultaneously, which is of benefit to assist in comprehensive clinical diagnosis. It also shows the potential to detect multiple drug resistance sites for precise treatment. However, considering the cost performance compared with conventional assays (especially Xpert MTB/RIF), mNGS seems to be over-qualified for patients with mild and typical symptoms. Technology optimization of sequencing and analyzing should be conducted to improve the positive rate and broaden the applicable fields.